Effects of ketamine on circadian rhythm and synaptic homeostasis in patients with treatment‐resistant depression: A protocol for mechanistic studies of its rapid and sustained antidepressant actions in humans. Issue 11 (15th October 2019) - Zhuo, Chuanjun; Tian, Hongjun; Li, Gongying; Chen, Min; Jiang, Deguo; Lin, Xiaodong; Xu, Yong; Wang, Wenqiang
Abstract: Background: The breakthrough discovery has been made that a single dose of ketamine, an N‐methyl‐D‐aspartate receptor antagonist, achieves rapid and sustained ( 7 days) antidepressant activity in patients with major depressive disorder (MDD). This discovery has ushered in an exciting era of research and brought new hope for patients with MDD. However, the mechanisms underlying the specific antidepressant actions of ketamine in humans remain to be elucidated. Objectives: This study protocol was designed to test the main hypothesis that ketamine could rapidly reverse depression‐ and stress‐associated synaptic loss and deficits in resting‐state functional connectivity and that this action could be affected by circadian rhythm, in patients with treatment‐resistant depression. Methods/Study Design: In this clinical study, adults (aged 18–65 years) with treatment‐resistant depression will be randomized to intravenous administration of placebo (control group) or ketamine (0.5 mg/kg body weight) at 11 a.m. (daytime group), or 6 p.m. (nighttime group) for 24 weeks. The primary outcome will be the change from baseline to 24 weeks in the total Montgomery‐Asberg Depression Rating Scale score. Brain imaging, sleep, and genetic studies, including functional magnetic resonance imaging, positron emission tomography, polysomnography, and genetic analyses, will be performed to examine whether and how ketamine can rapidly reverse deficits in synaptic function and to identify objective markers for the assessment of ketamine infusion therapy for treatment‐resistant depression. Conclusions: This clinical study protocol is the first, to our knowledge, to describe the prospective testing of the hypothesis that daytime and nighttime administrations of ketamine would have different antidepressant effects. The brain imaging, sleep, and genetic findings from patients with treatment‐resistant depression are expected to shed new light on the mechanisms of ketamine and its interaction with target sites in the brain, which can be used for objective evaluation of the efficacy of ketamine. Abstract : This clinical study protocol is the first, to our knowledge, to describe the prospective testing of the hypothesis that daytime and nighttime administrations of ketamine would have different antidepressant effects. The brain imaging, sleep, and genetic findings from patients with treatment‐resistant depression are expected to shed new light on the mechanisms of ketamine and its interaction with target sites in the brain, which can be used for objective evaluation of the efficacy of ketamine.